LITERASI BENCANA DI SEKOLAH: SEBAGAI EDUKASI UNTUK MENINGKATKAN PEMAHAMAN KEBENCANAAN - Labudasari, Erna; Rochmah, Eliya (Universitas Pendidikan Indonesia, 2020)
Indonesia is a country prone to natural disasters and many casualties. But along with this potential, it is not balanced with a good understanding of disaster, especially students at the elementary school level. The purpose of this study is to provide an overview and understanding of the importance of disaster literacy and the specifications of ways of prevention (pre-disaster), coping (post-disaster) and self-evacuation (emergency response) that can be done by elementary school students. This disaster literacy is a disaster mitigation effort so students know information about disasters and have an awareness of the potential for disasters that will occur, so they can prepare themselves and know how to deal with disasters. Through disaster literacy, it is expected to be able to shape the character of responsibility, preparedness and independence of students in the event of a disaster, as well as reduce disaster risk and minimize casualties from the children's sector.